Thyroid Parenchyma Microcalcifications on Ultrasound for Predicting Lymph Node Metastasis in Papillary Thyroid Carcinoma: A Prospective Multicenter Study in China - Liu, Juan; Jia, XiaoHong; Gu, Ying; Chen, Xia; Guan, Ling; Yan, JiPing; Zhai, Hong; Zhou, Na; Dong, YiJie; Zhan, WeiWei; Luo, XiaoMao; Zhou, JianQiao (Frontiers in Oncology, 2021)
Abstract Objective: Cervical lymph node metastasis (LNM) was found to be clinically significant prognostic factors of patients with papillary thyroid carcinomas (PTC). Ultrasound (US) characteristics of thyroid nodules and thyroid parenchyma may be used to predict LNM. To investigate the value of nodular US features as well as thyroid parenchymal microcalcifications on US in predicting LNM in patients with PTC. Methods: This prospective study was approved by the Institutional Review Board. From January 2018 to June 2019, 971 consecutive patients with solitary PTC who underwent preoperative neck US evaluation were included from six hospitals in China. The US features of thyroid nodules as well as thyroid parenchyma microcalcifications were carefully evaluated based on the static images and dynamic clips. Univariate and multivariate analyses were performed to determine independent predictors of LNM. Results: Of the 971 patients, 760 were female, 211 were male. According to the pathological examination, 241(24.82%) patients were found with cervical LNM (LNM positive group), while 730 (75.18%) patients were not (LNM negative group). Multiple logistic regression analysis showed that young age (<55 years old) (OR=1.522, P=0.047), large size (>10mm) (OR=1.814, P<0.001), intratumoral microcalcifications (OR=1.782, P=0.002) and thyroid parenchyma microcalcifications (OR=1.635, P=0.046) were independent risk factors for LNM of PTC. Conclusions: Young age, large nodule size, intratumoral microcalcifications, as well as thyroid parenchyma microcalcifications on US are independent predictors of cervical LNM for patients with PTC.